Trade and Financial Spilloveron Hong Kong SAR from a Downturn in Europe and Mainland China - N'Diaye, Papa.; Ahuja, Ashvin (Washington, D.C. : International Monetary Fund, 2012)
Hong Kong SAR was hit hard by the global financial crisis, which started out in the U.S. and spilled over to the rest of the world. Three years later, vulnerabilities in the euro area's financial system and concerns over a hard landing in Mainland China have started to weigh on Hong Kong's growth prospects. Against this backdrop, this paper aims to quantify the trade and financial spillovers on Hong Kong SAR's economy from a downturn in the euro area and Mainland China. Based on simulations using a version of the Global Integrated Monetary and Fiscal (GIMF) model and a Global VAR (GVAR) that includes both balance sheet and standard macroeconomic indicators, Hong Kong SAR's output growth could fall by as much as 1 1\2 times the decline in euro area output growth given its high dependence on external trade and many links with the global financial system. A worsening of the crisis in the euro area could reduce Hong Kong SAR's output by as much as 4-4 1\2 percent below baseline during the first two years after the shock, pushing Hong Kong SAR back into recession and possible deflation. In the event of a hard landing in China, the model simulations suggest that Hong Kong SAR would be on a sustained downturn with output growth falling by about 3 percentage points below baseline in the first two years. Should these events materialize, countercyclical fiscal response could help cushion, but not fully offset, the impact of slower growth in the euro area or China.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet